Foreign aid - real exchange rate nexus: Empirical evidence from Ghana - Derick Taylor Adu; Elisha Kwaku Denkyirah (Cogent Economics & Finance, 2018)
The contentious effect of foreign aid on real exchange rate in developing countries leading to Dutch disease necessitates further research since its impact can only be determined empirically. Using annual data gathered from the World Bank Development Index database with reference period of 1980 to 2016, we test the Dutch disease hypothesis by empirically examining the effect of foreign aid on real exchange rate in Ghana. Contrary to the findings of studies which establish non-existence of Dutch disease in Ghana, the empirical results of this study reveal otherwise, both in the short-run and long-run. To mitigate Dutch disease menace in Ghana, it is important that the country utilize its ideal productive capacity to cushion its aid-induced increased demand.
Keywords: 330; Dutch disease; foreign aid; Ghana; real exchange rate